2021
DOI: 10.3847/1538-4357/abda39
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Survey of Reservoir Phenomenon in Energetic Proton Events Observed by Multiple Spacecraft

Abstract: In this work, reservoir phenomenon in the decay phase of gradual solar energetic particle (SEP) events are investigated with two Helios and the IMP 8 spacecraft from 1976 January to 1980 March and two STEREO and the SOHO spacecraft from 2010 January to 2014 September. Using these data, 62 reservoir events of solar energetic protons were identified, and the effects of perpendicular diffusion and magnetic mirroring on the formation of the reservoir phenomenon have been studied. We find that the reservoir events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In this case, the magnetic connection between the spacecraft and the source diffusion region is not good. According to previous results (Zhang et al 2009;Lario 2010;Qin et al 2013;Wang et al 2021), the very slow increase of particle intensity observed by the SOHO spacecraft is probably caused by the interplanetary perpendicular diffusion. In interplanetary space, perpendicular diffusion could be much slower than parallel diffusion, which could explain the slow increase in particle intensity during the rising phase and the equal intensity of particles observed at different locations during the decay phase in this case.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In this case, the magnetic connection between the spacecraft and the source diffusion region is not good. According to previous results (Zhang et al 2009;Lario 2010;Qin et al 2013;Wang et al 2021), the very slow increase of particle intensity observed by the SOHO spacecraft is probably caused by the interplanetary perpendicular diffusion. In interplanetary space, perpendicular diffusion could be much slower than parallel diffusion, which could explain the slow increase in particle intensity during the rising phase and the equal intensity of particles observed at different locations during the decay phase in this case.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, after entering the decay phase of SEP intensities, the intensities observed by the three spacecraft are close to each other, implying that perpendicular diffusion plays an important role during particle propagation. The phenomenon, called the "reservoir" effect, is illustrated and discussed in detail in Anastasiadis et al (2019) and Wang et al (2021). In addition, the particular SEP event has been analyzed by many authors (see references in Anastasiadis et al 2019).…”
Section: Statistical Resultsmentioning
confidence: 99%
“…This can be explained by the so-called "reservoir phenomenon" (Roelof et al 1992;Reames et al 1997), which argues that in the late phase of large SEP events, the SEPs are nearly uniformly distributed throughout the inner heliosphere. Recent studies suggested that magnetic mirroring and the effect of perpendicular diffusion are important in the reservoir phenomenon (Wang et al 2021).…”
Section: Comparison Of Proton Time-intensity Profilesmentioning
confidence: 99%
“…This could also include a particle reservoir effect (e.g. Wang et al (2021); Anastasiadis, Lario, Papaioannou, Kouloumvakos, and Vourlidas (2019), and references therein) in the inner heliosphere which may have contributed to the prolonged duration of the SEP event at STEREO A and Mars.…”
Section: Accepted Articlementioning
confidence: 99%